An Exploration of Lecturer Strategies in Managing Language Skills Courses Using Online Learning During The Pandemic Covid-19: A Case Of Brawijaya University-Indonesia - Adi, Sugeng Susilo (Innovare Journal of Education, 2022)
This article describes the online learning strategy for language skills in the English Language Education Study Program of Brawijaya University-Indonesia during the COVID-19 pandemic. This research is exploratory qualitative research that uses observation and interviews as a way to obtain data. The data and information obtained are used as a basis in discussing this research problem with descriptive analysis. All lecturers take advantage of the available learning facilities by implementing synchronous and asynchronous learning sessions. Some information was obtained from interviews with lecturers stating that in using synchronous sessions, the lecturers use the Zoom, Google Meet, and VLM facilities to manage teleconference model lectures. Meanwhile, lecturers use the Google Classroom facility to carry out various activities in using asynchronous sessions, including sending reading assignments, projects, online discussions, and sending asynchronous class schedules. One of the learning strategies in this research is the strategy of managing the online learning process. In the strategy of managing learning, creating student discipline, in this case, so that students actively participate by turning on the camera in a synchronous session, is needed to create meaningful interactions. At last, the researcher suggests further research to develop language skills courses and pedagogy courses.